Pengembangan Bahan Ajar Buku Teks IPS Tema Indahnya Kebersamaan Pada Peserta Didik Kelas 4 MI An Nuriyah Kwanyar Bangkalan - Faqih, Nurul Makrifah; Fauzi, Nur (LPPM Sekolah Tinggi Agama Islam Al Azhar, 2020)
This research aims to develop Social Science Textbook teaching materials. The material teaching is developed in the form of social studies textbooks with the theme